2016
DOI: 10.4236/ojgen.2016.62005
|View full text |Cite
|
Sign up to set email alerts
|

Computational Molecular Analysis of the Sequences of BMP15 Gene of Ruminants and Non-Ruminants

Abstract: Bone morphogenetic protein 15 (BMP15) is a member of the transforming growth factor β (TGFβ) super family that is expressed by oocytes and plays key roles in granulosa cell development and fertility in animal. This study investigated the molecular genetic variation of BMP15 gene of some selected mammalian species with a view to providing relevant genetic information for breeding and selection programmes in the studied species using computational methods. A total of thirty seven (37) BMP15 nucleotide sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…For the GDF9 gene, the sample sequence (G1DNA GDF9F) is closer to the sequence of Egyptian Rahmani sheep (NCBI accession no: KT357481.1) than the sequence of Egyptian crossbred (Suffolk × Awassi) (NCBI accession no: KT357485.1) and Pelibuey sheep (NCBI accession no: KT853039.1) (Argüello-Hernández et al 2014). The findings were similar to the phylogeny results of previous studies (for example, Bibinu et al 2016) of BMP15 gene, who reported a similar clustering of sequences among the various breeds, although there was some intermingling process between the species. The phylogenetic relationship of these two investigated genes indicated that, the indigenous sheep of Bangladesh is similar to the sheep of Mexico, North America and Egypt.…”
Section: Evolutionary Relationships (Phylogenetic Tree) Taxa Of Bmp15supporting
confidence: 91%
“…For the GDF9 gene, the sample sequence (G1DNA GDF9F) is closer to the sequence of Egyptian Rahmani sheep (NCBI accession no: KT357481.1) than the sequence of Egyptian crossbred (Suffolk × Awassi) (NCBI accession no: KT357485.1) and Pelibuey sheep (NCBI accession no: KT853039.1) (Argüello-Hernández et al 2014). The findings were similar to the phylogeny results of previous studies (for example, Bibinu et al 2016) of BMP15 gene, who reported a similar clustering of sequences among the various breeds, although there was some intermingling process between the species. The phylogenetic relationship of these two investigated genes indicated that, the indigenous sheep of Bangladesh is similar to the sheep of Mexico, North America and Egypt.…”
Section: Evolutionary Relationships (Phylogenetic Tree) Taxa Of Bmp15supporting
confidence: 91%
“…The neutral substitution is a clear indication that the substitution did not impair the protein structure in terms of structure and function which will help in prevention of susceptibility to disease and also give hope for future selection while the deleterious dose the opposite. 15 Since the amino acid substitution in this study revealed both neutral and deleterious variants, this implies that any attempt to increase the number of beneficial allele there is high frequency of also increasing deleterious allele. The modern genetic analysis of determining singly nucleotide polymorphism offer great hope for future selection stock as it enable to chosen molecular markers for selection.…”
Section: Discussionmentioning
confidence: 79%
“…Out of the fifteen (15) amino acid substitutions in all the six studied species, five were deleterious in water buffalo and pig, six in goat and sheep, ten in camel and one in cattle while the remaining 10, 9, 5 and 14 amino acid substitutions were neutral for water buffalo and pig, goat and sheep, camel and cattle respectively. The amino acid substitution that returned neutral indicates that the substitution did not have any damaging effect on the structure and function of the protein while those deleterious amino acid substitution predictions were harmful and could cause an alteration or impairment of protein functions which may lead to impair energy balance, low levels of circulating fatty acid, adipocyte hypertrophy, lipid-filled macrophages and an increase in basal lipolysis particularly in lactating animals [20,21,22]. This is because the synthesis of milk components involves the mobilization of lipid depots to satisfy the large energy demands of the mammary gland [8].…”
Section: Discussionmentioning
confidence: 99%